If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -3p = -2 Solving 4 + -3p = -2 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3p = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -3p = -2 + -4 -3p = -2 + -4 Combine like terms: -2 + -4 = -6 -3p = -6 Divide each side by '-3'. p = 2 Simplifying p = 2
| 10v=60 | | 2(3-w)+6=-6(w-2)-7 | | 0(-8/7) | | X^2=34X | | -6/7w=-42 | | 4x^2-24x=-27 | | -8/15-23/25 | | 1/3(3x-9)=-10+6+3(2-x) | | 6(2x+1)=10x+4 | | 12x-10=10x-6 | | 0=4(-4x^2+10x-6) | | 3(x+14)=69 | | z^2+6z-27=0 | | -36=4v+4(v+7) | | 5/6*2/3=x | | -19/35+4/15 | | 3x^2+5=65 | | 9=3x-7 | | -120x+3000=-160x+4000 | | 7+2x=5x-5 | | 4x+2=32 | | 67-3x=9x+16 | | 7/9y+2+5/9y+6 | | 3a+2a=135 | | x-.3x=105 | | 4+8r-3=7r+29-3r | | 6z+18-9=27 | | 5y-5y=-5 | | 22+k=29 | | 4x+3x=9 | | -3z+6z=9z+9-4z | | ln(x)=ln(2)+ln(x-8) |